Comparison Between Mini PCNL and Standard PCNL in Management of Nephrolithiasis - Bhandari, Bharat Bahadur; Thapa, Bikash Bikram; Ayer, Dhirendra; Thapa, Suresh; Bista, Sanjeeb (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: The incidence of small and medium size renal stones is rising. Stone clearance, bleeding, urine leak and infectious complications are major concerns for urologist. Urologist chooses best technique from list of armamentarium available. Minimally invasive approach like Percutaneous Nephrolithotomy (PCNL) has significantly influenced the renal stone management since 1976. Miniaturisation of the instruments allow more effective and safer alternatives for urolithasis management. Methods: This is a retrospective study in which the outcome of mini PCNL (mPCNL) was compared with standard PCNL (sPCNL) in management of nephrolithiasis. Result: There were no significant difference in stone free rate between mPCNL and sPCNL (96.2 ± 3.6% vs 95.3 ± 4.8%). The total operative time was longer in mPCNL (55.2 ± 19.0 minute vs 62 ± 21.0 minute) but the difference was not statistically significant. Conclusions: Mini PCNL is as effective as standard PCNL with fewer bleeding complications in management of medium sized nephrolithiasis.